Comparative Perspectives on School Textbooks Analyzing Shifting Discourses on Nationhood, Citizenship, Gender, and Religion - Hildebrandt-Wypych, Dobrochna; Wiseman, Alexander W. (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XXXIV, 359 p. 17 illus., 2 illus. in color.